(untitled) (Sunari Penjor : Journal of Anthropology, 2025)
This study is motivated by the shift in consumer preferences, where people now tend to favor modern and fast food, thereby threatening the existence of traditional foods such as ombus-ombus. The ombus-ombus vendors in Siborongborong District, North Tapanuli Regency, face various challenges such as declining customer interest, market competition, rising prices of raw materials, limited capital, and government regulations. The aim of this study is to identify those challenges, the survival strategies used by the vendors, and the driving factors behind their persistence in running the business. This research uses a descriptive qualitative method with data collection techniques through observation, in-depth interviews, and documentation. The results show that vendors survive by innovating their presentation, maintaining taste quality, building good relationships with customers, and remaining loyal to their cultural heritage. The main driving factors include economic necessity, emotional attachment, and cultural values. The analysis is based on Max Weber’s theory of social action, which examines rational action through instrumental, value-oriented, traditional, and affective dimensions.